Analisis Faktor Rendahnya Minat Belajar Matematika Siswa MA Plus Nurul Islam Sekarbela - Husnul Hatimah; Dedi Riyan Rizaldi; Dewi Sartika; Sripatmi; Nilwan; Ziadatul Fatimah (Action Research Journal, 2024)
This study aims to analyze the factors that cause low interest in learning mathematics in students at MA Plus Nurul Islam Sekarbela and explore efforts that can be made to overcome these factors. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the level of student interest in learning varies, where some students show a high interest in mathematics, while others have difficulty understanding the material so that they are less motivated. Factors that inhibit interest in learning include difficulty in understanding complex material, limited learning time, lack of additional learning resources, less interesting teaching methods, and minimal use of technology in learning. The conclusion of this study shows that to increase interest in learning mathematics, it is necessary to use technology-based media, contextual and project-based learning approaches, and provide additional learning resources. The implementation of this strategy is expected to increase student involvement and motivation in learning mathematics at MA Plus Nurul Islam Sekarbela